2021
DOI: 10.1002/advs.202101824
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Atomic Fe‐N‐C Materials and Dual Roles Investigation of Fe‐N4 Sites in Fenton‐Like Reactions

Abstract: Fenton-like reactions with persulfates as the oxidants have attracted increasing attentions for the remediation of emerging antibiotic pollutions. However, developing effective activators with outstanding activities and long-term stabilities remains a great challenge in these reactions. Herein, a novel activator is successfully synthesized with single iron atoms anchored on porous N-doped carbon (Fe-N-PC) by a facile chemical vapor deposition (CVD) method. The single Fe atoms are coordinated with four N atoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(53 citation statements)
references
References 51 publications
3
42
1
Order By: Relevance
“…The peak at 21.4° could be assigned to amorphous carbon, and the other two peaks are corresponding to the (002) and (100) characteristic planes of graphitic carbon. 22,41 The intensity ratio of the peaks at 26° and 21.4° gradually increases with the deposition temperature acceleration, indicating that the degree of graphitization is enhanced. The graphitization degree and defect levels of all samples were characterized by Raman spectrometer.…”
Section: Resultsmentioning
confidence: 98%
“…The peak at 21.4° could be assigned to amorphous carbon, and the other two peaks are corresponding to the (002) and (100) characteristic planes of graphitic carbon. 22,41 The intensity ratio of the peaks at 26° and 21.4° gradually increases with the deposition temperature acceleration, indicating that the degree of graphitization is enhanced. The graphitization degree and defect levels of all samples were characterized by Raman spectrometer.…”
Section: Resultsmentioning
confidence: 98%
“…X-ray absorption nearedge structure (XANES) spectrum of Fe-SA-NrGO suggested that Fe K-edge was located between FeO (Fe II ) and Fe 2 O 3 (Fe III ), which indicated that the oxidation valence of Fe in Fe-SA-NrGO ranged from +2 to +3 (Figure 3d). [21] Considering the position of the absorption edge, it was clear that the different light elements such as N/O coexistence were coordinated with single-Fe atoms. The Fourier-transformed k 3 -weighted extended X-ray absorption fine structure (EXAFS) image displayed two main peaks at 1.97 and 2.89 Å, which were assigned to the first coordination shell of FeN/O and second coordination shell of FeNC, respectively (Figure 3e and Figures S10 and S11, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike conventional crystalline catalysis, atomically dispersed catalysts possess extensive catalytically active sites, 30,32 owing to the utmost atomic utilization, and thus the high metal loading often reflects the superior catalytic performance. 26 As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The high defect level endows the catalyst with more active sites, and it facilitates the acquisition of electrons by electrophilic peroxides. 38,39 Unlike conventional crystalline catalysis, atomically dispersed catalysts possess extensive catalytically active sites, 30,32 owing to the utmost atomic utilization, and thus the high metal loading often reflects the superior catalytic performance. 26 As shown in Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation